Determination of sdLDL particles in patients with Familial Hyercholesterolaemia and Familial Combined Hyperlipidaemia - Gomes, A. (2011)
Several studies demonstrated that sdLDL are an emerging cardiovascular (CV) risk factor. The objective of this study was sdLDL measurement in patients with genetic diagnosis of Familial Hypercholesterolaemia (FH) and clinical diagnosis of Familial Combined Hyperlipidaemia (FCHL) to establish a relation between sdLDL, CV risk and the efficacy of therapeutics. Lipid profile was determined using a polyacrylamide gel electrophoresis system that separates the particles in serum that contain cholesterol. The lipidogram obtained classifies the patients as being profile A (low CV risk) or B (high CV risk) depending on the sdLDL concentration. The lipid profile was obtained from 43 FH adults and 46 FCHL adults, index and relatives. FH and FCHL patients without medication and with high sdLDL (>6mg/dl) have significant higher levels of total cholesterol, LDL and ApoB and FCHL patients also have significant higher triglycerides, compared to FH and FCHL patients with sdLDL levels under recommended values. Under medication FH patients have significant higher ApoB levels and lower HDL, and FCHL patients have significant higher total cholesterol, LDL and ApoB levels. Interestingly, 71,4% of FCHL patients under medication presented high CV risk profile, showing that statins seem not to decrease sdLDL levels and neither CV risk. Also FCHL patients are not well medicated or do not respond to usual medication to decrease cholesterol. These preliminary results indicate that sdLDL could be a good biomarker for treatment control but further studies are needed to evaluate the effect of medication in sdLDL levels in FH and FCHL patients.